Timing of antibiotic initiation in sepsis and neutropenic fever - Gretland, Jenny; Sjømæling, Sigrun; Mosevoll, Knut Anders; Reikvam, Håkon (Frontiers in Medicine, 2025)
IntroductionSepsis, as a life-threatening organ dysfunction caused by a dysregulated host response to infection, remains a leading cause of mortality worldwide. The condition requires rapid treatment, and The Surviving Sepsis Campaign from 2021 recommend administration of antimicrobials within one hour for suspected septic shock or high likelihood of sepsis.MethodsWe conducted a comprehensive review of the literature regarding timing of antimicrobial administration and its impact on sepsis outcome, to evaluate whether a 1 h target for initiating antibiotics is a reasonable goal. A literature search was conducted in the PubMed database, and we performed a narrative synthesis of the studies.ResultsOf the 42 studies reviewed, 34 demonstrated a significant association between delayed time to first antibiotic and increased mortality rates. The majority of the studies found a significant increase in mortality with delays in antimicrobial initiation, particularly with hourly cutoffs.DiscussionSepsis is a heterogeneous condition, complicating the establishment of universal guidelines. Approximately half of the studies identified a near-linear relationship between delayed antimicrobial treatment and increased mortality, emphasizing the benefit of administering antibiotics within 1 h. However, other studies did not observe this linear association, instead reporting significantly increased mortality only after 3–6 h. These findings may indicate that a 1 h goal may not be optimal for all patients.ConclusionBased on the findings in this systematic review, the recommendations outlined in The Surviving Sepsis Campaign appear to be reasonable goals. For patients with febrile neutropenia, further research is necessary to determine the optimal timing for antimicrobial administration.